Determination of Causes of Adolescent Restiveness and National Security in Northwest Nigeria - Maiwada, R. A.; Giginyu, A. A. (Journal of Research in Industrial Technology and Educational Studies, 2026)
This study analyzes the causes of adolescent restiveness in North-West, Nigeria. The objectives were to identify these causes, analyze the implications of youth restiveness, and determine the challenges hindering the adoption of mitigation strategies in the region. An ex-post facto research design was adopted. The study’s population comprised 25,139,426 youths living in North-West, Nigeria. Data were collected from a sample size of 384 respondents using a simple random sampling procedure. Primary data were gathered through structured questionnaires with a Likert scale and analyzed using descriptive statistics. The findings revealed that major causes of adolescent restiveness include negative psychological effects and insufficient access to basic needs. The implications of youth restiveness encompass the intensification of teenage criminal activities and the development of psychosomatic trauma. Challenges hindering the adoption of mitigation strategies include a lack of awareness regarding the importance of youth, deprived governance and negligence, and corruption in youth selection processes. The study recommended, among other things, that the government, in collaboration with philanthropists and other community stakeholders, should prioritize providing effective solutions to the root causes. Media programs and other stakeholders should organize consistent and regular sensitization programs. Government agencies and other stakeholders should collaborate to provide lasting resolutions to these challenges by introducing psychological and practical strategies to curb dissatisfaction.